Prussian blue positive electrode material and preparation method thereof, positive electrode plate, sodium ion battery and electric equipment
By preparing Prussian blue cathode materials with high crystallinity and low crystallization water, the problems of low crystallinity and high crystallization water in the prior art are solved, and the electrochemical performance and the cycle life of sodium ion batteries are significantly improved.
Patent Information
- Application Number
- CN202411530281.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-11
AI Technical Summary
The Prussian blue cathode material prepared by the existing methods has low crystallinity and high crystallization water, resulting in low electrochemical performance.
By dissolving the transition metal salt and disodium tartarate in deionized water, combining sodium ferrocyanide dehydrate and disodium tartarate solution, controlling the stirring and aging time, Prussian blue positive electrode with high crystallinity and low crystallization water was prepared. Material.
The preparation of Prussian blue materials with high crystallinity, low crystallization water and few defects has been achieved, which improves the electrochemical performance of the material and extends the cycle life of sodium ion batteries.
Smart Images

Figure CN119409210A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy technology, and in particular to a Prussian blue positive electrode material and a preparation method thereof, a positive electrode sheet, a sodium ion battery and an electrical device. Background Art
[0002] Common positive electrode materials for sodium ion batteries mainly include layered oxides, polyanionic compounds, Prussian blue analogs, etc. Among them, Prussian white (transition metal valence states are all divalent and the color is white) as a Prussian blue analog has an open framework system and porous structure compared with other positive electrode materials, which can allow sodium ions to be freely and quickly deintercalated, thereby effectively improving the electrochemical performance of sodium ion batteries.
[0003] However, the Prussian blue cathode materials prepared by the existing methods have low crystallinity, high crystal water content and low electrochemical performance. Summary of the invention
[0004] The purpose of the present application is to provide a Prussian blue positive electrode material and a preparation method thereof, a positive electrode plate, a sodium ion battery and an electrical device, aiming to solve the problem of low crystallinity and high crystal water content of the Prussian blue positive electrode material prepared by the existing method.
[0005] To achieve the above objectives, the present application provides a method for preparing a Prussian blue positive electrode material, comprising:
[0006] dissolving a transition metal salt and a first disodium tartrate in a first deionized water to obtain a first solution;
[0007] dissolving sodium ferrocyanide decahydrate and second disodium tartrate in second deionized water to obtain a second solution;
[0008] adding the first solution to the second solution to obtain a suspension;
[0009] The suspension is stirred and aged to obtain the Prussian blue positive electrode material.
[0010] In some embodiments, the usage ratio of the transition metal salt, the first disodium tartrate, and the first deionized water is 1 mol: (1-4) mol: (40-90) ml.
[0011] In some embodiments, at least one of the following conditions is met:
[0012] A. The transition metal salt includes at least one of a Mn salt, a Fe salt, a Co salt, a Ni salt, a Cu salt, and a Zn salt;
[0013] B. The transition metal salt includes at least one of sulfate, chloride, acetate, acetylacetonate and oxalate.
[0014] In some embodiments, the usage ratio of the sodium ferrocyanide decahydrate, the second disodium tartrate, and the second deionized water is 1 mol: (1-4) mol: (40-90) ml.
[0015] In some embodiments, at least one of the following conditions is met:
[0016] A. the speed at which the first solution is added to the second solution is 1 ml / min-10 ml / min;
[0017] B. The first solution is added to the second solution while stirring at a speed of 500 r / min-1000 r / min.
[0018] In some embodiments, at least one of the following conditions is met:
[0019] A. The stirring time is 10h-20h;
[0020] B. The aging time is 20-30h.
[0021] The present application also provides a Prussian blue-based positive electrode material, which is prepared by the above-mentioned method for preparing the Prussian blue-based positive electrode material.
[0022] The present application also provides a positive electrode plate, comprising the above-mentioned Prussian blue positive electrode material.
[0023] The present application also provides a sodium ion battery, comprising the above-mentioned positive electrode plate.
[0024] The present application also provides an electrical device, comprising the above-mentioned sodium ion battery.
[0025] Compared with the prior art, the beneficial effects of this application include:
[0026] The preparation method of the Prussian blue cathode material provided by the present application is to prepare a Prussian blue material with high crystallinity, low crystal water and few defects by using disodium tartrate one-step method, and the method is simple and the cost is low. Disodium tartrate exists simultaneously in a salt solution and a sodium ferrocyanide solution, and the same pH and complexing ability can be maintained when a transition metal salt is dripped from a first solution into a second solution. The first solution and the second solution are weakly alkaline, rich in a large amount of tartrate ions, and tartrate ions are rich in abundant -OH, so that it can be used as a strong complexing agent, and each single tartrate ion can complex a single transition metal ion to form a transition metal-tartrate complex, which can significantly reduce the release rate of the transition metal, thereby affecting its binding rate with ferrocyanide, and slowly combining, crystal growth can be made more sufficient, thereby reducing the content of ferrocyanide and crystal water.
[0027] In addition, disodium tartrate provides two sodium sources. After disodium tartrate is hydrolyzed, sodium ions are evenly distributed throughout the solution, showing an emulsifying effect, which can achieve a slow crystallization effect. During the reaction of sodium ferrocyanide and transition metal salts, the sodium ions dissociated from disodium tartrate will crystallize together, thereby obtaining Prussian blue crystals with high sodium content, low defects and high crystallinity. At the same time, the sodium-rich environment reduces the probability of water molecules entering the crystals. In addition, disodium tartrate molecules will form a salt-in-water structure at high concentrations, which makes it difficult for water molecules to move during the synthesis reaction, thereby reducing the content of crystal water in the material.
[0028] In addition, disodium tartrate acts as a surfactant and induces the growth direction of the crystal structure. The synthesized materials are all nanoscale, with an observed particle size of approximately 500-800nm and a multilayer cubic structure with uniform particles.
[0029] The Prussian blue positive electrode material provided in the present application has high crystallinity, low crystal water, and few defects.
[0030] The positive electrode plate, sodium ion battery and electrical equipment provided by the present application have a long cycle life due to the use of the Prussian blue positive electrode material of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0032] Figure 1 A schematic diagram of a process for preparing a Prussian blue cathode material of the present application;
[0033] Figure 2 This is a SEM image of the Mn-based Prussian blue cathode material of Example 1;
[0034] Figure 3 This is the weight loss curve of the Mn-based Prussian blue cathode material of Example 1;
[0035] Figure 4 is the charge and discharge voltage platform of the button-type full battery of Example 1;
[0036] Figure 5 The electrochemical performance test result diagram of the button-type full battery of Example 1;
[0037] Figure 6 This is the SEM image of the Mn-based Prussian blue positive electrode material of Comparative Example 2. DETAILED DESCRIPTION
[0038] As used herein:
[0039] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0040] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0041] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0042] In these examples, parts and percentages are by mass unless otherwise indicated.
[0043] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0044] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0045] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0046] This application provides a method for preparing a Prussian blue positive electrode material. Figure 1 ,include:
[0047] S100: dissolving a transition metal salt and a first disodium tartrate in first deionized water to obtain a first solution.
[0048] S200: dissolving sodium ferrocyanide decahydrate and disodium tartrate in second deionized water to obtain a second solution.
[0049] S300: adding the first solution into the second solution to obtain a suspension.
[0050] S400: stirring and aging the suspension to obtain a Prussian blue positive electrode material.
[0051] Wherein, the first disodium tartrate and the second disodium tartrate are both disodium tartrate, and the first and second are only used to distinguish the description. Disodium tartrate exists in the salt solution and the sodium ferrocyanide solution at the same time, so that the transition metal salt can maintain the same pH and complexing ability when it is dripped from the first solution into the second solution. The first solution and the second solution are weakly alkaline, rich in a large amount of tartrate ions, and the tartrate ions are rich in -OH, so that they can be used as strong complexing agents, and each single tartrate ion can complex a single transition metal ion to form a transition metal-tartrate complex, which can significantly reduce the release rate of the transition metal, thereby affecting its binding rate with ferrocyanide, and the slow combination will make the crystal growth more sufficient, thereby reducing the content of ferrocyanide and water of crystallization.
[0052] In addition, disodium tartrate provides two sodium sources. After disodium tartrate is hydrolyzed, sodium ions are evenly distributed throughout the solution, showing an emulsifying effect, which can achieve a slow crystallization effect. During the reaction of sodium ferrocyanide and transition metal salts, the sodium ions dissociated from disodium tartrate will crystallize together, thereby obtaining Prussian blue crystals with high sodium content, low defects and high crystallinity. At the same time, the sodium-rich environment reduces the probability of water molecules entering the crystals. In addition, disodium tartrate molecules will form a salt-in-water structure at high concentrations, which makes it difficult for water molecules to move during the synthesis reaction, thereby reducing the content of crystal water in the material.
[0053] In addition, disodium tartrate acts as a surfactant and induces the growth direction of the crystal structure. The synthesized materials are all nanoscale, with an observed particle size of approximately 500-800nm and a multilayer cubic structure with uniform particles.
[0054] Prussian blue-type materials have low crystallinity, which leads to unstable crystal structure of the material. The crystals are prone to collapse and distortion during the charge and discharge process, thereby reducing the effective sodium storage space. If the crystal water is too high, the effective sodium storage sites in the material will be occupied by water, reducing the sodium content in the crystal structure. Therefore, Prussian blue-type materials with low crystallinity and high crystal water often exhibit lower electrochemical performance.
[0055] The preparation method of the Prussian blue positive electrode material provided in the present application uses disodium tartrate in a one-step method to prepare a Prussian blue material with high crystallinity, low crystal water and few defects. The method is simple and low in cost.
[0056] In some embodiments, the usage ratio of the transition metal salt, the first disodium tartrate, and the first deionized water in step S100 is 1 mol: (1-4) mol: (40-90) ml, for example, it can be 1 mol: 1 mol: 50 ml, or 1 mol: 2 mol: 50 ml, or 1 mol: 3 mol: 50 ml, or 1 mol: 4 mol: 50 ml, or any value in between 1 mol: (1-4) mol: (40-90) ml.
[0057] In some embodiments, the dosage ratio of sodium ferrocyanide decahydrate, the second disodium tartrate, and the second deionized water in step S200 is 1 mol: (1-4) mol: (40-90) ml, for example, it can be 1 mol: 1 mol: 50 ml, or 1 mol: 2 mol: 50 ml, or 1 mol: 3 mol: 50 ml, or 1 mol: 4 mol: 50 ml, or any value in between 1 mol: (1-4) mol: (40-90) ml.
[0058] If the concentration of disodium tartrate in the first solution and the second solution is lower than this range, it will not be able to play a good complexing role and form a good salt-in-water structure, which will lead to an increase in the content of crystal water in the material. In addition, the particle size will also change significantly, from 500-800nm to 5-10μm. If the concentration of disodium tartrate in the first solution and the second solution is higher than this range, it will lead to the precipitation of disodium tartrate after the material reaction, and it will be adsorbed and residual on the surface of the material, so that the main material part that provides the capacity of the reagent is reduced, which is not conducive to mass production.
[0059] In some embodiments, the transition metal salt includes at least one of a Mn salt, a Fe salt, a Co salt, a Ni salt, a Cu salt, and a Zn salt.
[0060] In some embodiments, the transition metal salt includes at least one of a sulfate, a chloride, an acetate, an acetylacetonate, and an oxalate.
[0061] In some embodiments, the first solution is added to the second solution at a speed of 1 ml / min-10 ml / min; the first solution is stirred while being added to the second solution, and the stirring speed is 500 r / min-1000 r / min.
[0062] In some embodiments, the stirring time is 10h-20h; the aging time is 20-30h.
[0063] The present application also provides a Prussian blue-based positive electrode material, which is prepared by the above-mentioned method for preparing the Prussian blue-based positive electrode material.
[0064] The Prussian blue positive electrode material provided in the present application has high crystallinity, low crystal water, and few defects.
[0065] The present application also provides a positive electrode plate, comprising the above-mentioned Prussian blue positive electrode material.
[0066] The present application also provides a sodium ion battery, comprising the above-mentioned positive electrode plate.
[0067] The present application also provides an electrical device, comprising the above-mentioned sodium ion battery.
[0068] The positive electrode plate, sodium ion battery and electrical equipment provided by the present application have high specific capacity and long cycle life due to the use of the Prussian blue positive electrode material of the present application.
[0069] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0070] Example 1
[0071] This embodiment first provides a Mn-based Prussian blue positive electrode material, and the preparation method thereof comprises the following steps:
[0072] Take 5mmol of MnSO4 and 15mmol of disodium tartrate and dissolve them in 50ml of deionized water to form solution A. Take 5.1mmol of sodium ferrocyanide decahydrate and 15mmol of disodium tartrate and dissolve them in 50ml of deionized water to form solution B. Use a peristaltic pump to drip solution A into solution B at a flow rate of 5ml / min, while ensuring that the stirring speed is 800r / min. After the addition is completed, stir for 16h and then age for 24h to obtain a Mn-based Prussian blue cathode material with a chemical formula of Na2Mn[Fe(CN)6], and its SEM picture is as follows Figure 2 As shown, Figure 2 The right part in the middle is a partial enlarged view of the left part. The weight loss curve is as follows Figure 3 shown.
[0073] This embodiment also provides a positive electrode sheet, and the preparation method thereof includes the following steps:
[0074] Take the Mn-based Prussian blue positive electrode material, PVDF (polyvinylidene fluoride), and conductive carbon black obtained in Example 1 in a mass ratio of 8:1:1. First, weigh the above materials in proportion and place them in a small weighing bottle (2.5cm*2.5cm), add a certain amount of NMP (N-methylpyrrolidone) solution, stir for 6 hours, and apply the stirred slurry on a stainless steel foil. After coating, place it in a vacuum drying oven and dry it at 120°C for 8 hours. Then use a cutting machine to cut it into small disc electrode sheets with a diameter of 16mm and compact it under a pressure of 10Mpa. Ensure that the mass of the Prussian blue analog active substance on this electrode is about 1.2mg / cm 2 The above process obtains the positive electrode sheet of the button battery.
[0075] This embodiment also provides a negative electrode sheet, and the preparation method thereof includes the following steps:
[0076] Preparation of negative electrode material: Take 2.0gNaH2PO2, 2.0gH2TiO3, 2.0H3PO4 and add them to 2.0ml deionized water, stir at 800r / min for 5min to mix evenly, transfer to a 50ml high-pressure reactor, keep warm at 140℃ for 6h, heating rate is 5℃ / min, centrifuge to obtain white precipitate. Dry overnight at 60℃ in a vacuum oven to obtain NaTi2(PO4)3 precursor. Take 2.0g of the prepared NaTi2(PO4)3 precursor and 0.1g of glucose into a mortar, take 5ml of anhydrous ethanol solution and grind for 5-10min. Then transfer to a ball mill, ball mill for 10-20min, take out the powder, place it in a vacuum oven, carbonize at 600℃ for 6h at a heating rate of 5℃ / min, and finally obtain carbon-coated NaTi2(PO4)3 negative electrode material.
[0077] Preparation of negative electrode: Take the prepared sodium titanium phosphate, conductive carbon black, and PVDF (polyvinylidene fluoride) in a mass ratio of 7:2:1. First, weigh the above materials in proportion and place them in a small weighing bottle (2.5cm*2.5cm), add 17 drops of NMP (N-methylpyrrolidone) solution, stir for 4 hours, apply the stirred slurry on the copper foil, place it in a vacuum drying oven after coating, dry it for 8 hours, and then use a cutting machine to cut it into small disc electrode sheets with a diameter of 16mm, and compact it under a pressure of 10Mpa. Ensure that the mass of active material on this electrode is about 2.1mg / cm 2 About, ensure that the positive and negative electrode capacity ratio is 1: (1.2-2.0).
[0078] Single electrode test: The single electrode test system is Shanghai Chenhua CHI660e electrochemical workstation, the working electrode is the prepared positive and negative electrode sheets, the counter electrode is a Pt sheet electrode, and the reference electrode is a saturated calomel electrode (Hg2Cl2 and KCl). The positive electrode test voltage is 0~1.0V, and the negative electrode test voltage is 0~-1V.
[0079] This embodiment also provides a full battery, and the preparation method thereof comprises the following steps:
[0080] The full battery uses 2025 button cells, and the installation order is negative electrode shell, spring, gasket, negative electrode plate, electrolyte (17m NaClO4), diaphragm (260μm thick glass fiber diaphragm), electrolyte (17m NaClO4), positive electrode plate, gasket, positive electrode shell.
[0081] Full battery test: The charge and discharge cycle test was carried out on the Newwell battery test system, with the test voltage range of 0.01-1.9V and a constant temperature of 25°C. The charge and discharge voltage platform of the button-type full battery of Example 1 is as follows: Figure 4 The electrochemical performance test results are shown in Figure 5 shown.
[0082] Example 2
[0083] This embodiment provides an Fe-based Prussian blue positive electrode material, and the preparation method thereof comprises the following steps:
[0084] Take 5mmol of FeSO4 and 15mmol of disodium tartrate and dissolve them in 50ml of deionized water to form solution A, and take 5.1mmol of sodium ferrocyanide decahydrate and 15mmol of disodium tartrate and dissolve them in 50ml of deionized water to form solution B. Use a peristaltic pump to drip solution A into solution B at a flow rate of 5ml / min, while ensuring that the stirring speed is 800r / min. After the addition is completed, stir for 16h and then age for 24h to obtain an Fe-based Prussian blue cathode material with a chemical formula of Na2Fe[Fe(CN)6].
[0085] The preparation method and testing method of the positive electrode sheet, negative electrode sheet and full battery of this embodiment are the same as those of Embodiment 1 and will not be repeated here.
[0086] Example 3
[0087] This embodiment provides a Co-based Prussian blue positive electrode material, and the preparation method thereof comprises the following steps:
[0088] Take 5mmol of CoSO4 and 15mmol of disodium tartrate and dissolve them in 50ml of deionized water to form solution A. Take 5.1mmol of sodium ferrocyanide decahydrate and 15mmol of disodium tartrate and dissolve them in 50ml of deionized water to form solution B. Use a peristaltic pump to drip solution A into solution B at a flow rate of 5ml / min, while ensuring that the stirring speed is 800r / min. After the addition is completed, stir for 16h and then age for 24h to obtain a Co-based Prussian blue cathode material with a chemical formula of Na2Co[Fe(CN)6].
[0089] The preparation method and testing method of the positive electrode sheet, negative electrode sheet and full battery of this embodiment are the same as those of Embodiment 1 and will not be repeated here.
[0090] Example 4
[0091] This embodiment provides a Ni-based Prussian blue positive electrode material, and the preparation method thereof comprises the following steps:
[0092] Take 5mmol of NiSO4 and 15mmol of disodium tartrate and dissolve them in 50ml of deionized water to form solution A, take 5.1mmol of sodium ferrocyanide decahydrate and 15mmol of disodium tartrate and dissolve them in 50ml of deionized water to form solution B. Use a peristaltic pump to drip solution A into solution B at a flow rate of 5ml / min, while ensuring that the stirring speed is 800r / min. After the addition is completed, stir for 16h and then age for 24h to obtain a Ni-based Prussian blue cathode material with a chemical formula of Na2Ni[Fe(CN)6].
[0093] The preparation method and testing method of the positive electrode sheet, negative electrode sheet and full battery of this embodiment are the same as those of Embodiment 1 and will not be repeated here.
[0094] Example 5
[0095] This embodiment provides a Cu-based Prussian blue positive electrode material, and the preparation method thereof comprises the following steps:
[0096] Take 5mmol of CuSO4 and 15mmol of disodium tartrate and dissolve them in 50ml of deionized water to form solution A. Take 5.1mmol of sodium ferrocyanide decahydrate and 15mmol of disodium tartrate and dissolve them in 50ml of deionized water to form solution B. Use a peristaltic pump to drip solution A into solution B at a flow rate of 5ml / min, while ensuring that the stirring speed is 800r / min. After the addition is completed, stir for 16h and then age for 24h to obtain a Cu-based Prussian blue cathode material with a chemical formula of Na2Cu[Fe(CN)6].
[0097] The preparation method and testing method of the positive electrode sheet, negative electrode sheet and full battery of this embodiment are the same as those of Embodiment 1 and will not be repeated here.
[0098] Example 6
[0099] This embodiment provides a Zn-based Prussian blue positive electrode material, and the preparation method thereof comprises the following steps:
[0100] Take 5mmol of ZnSO4 and 15mmol of disodium tartrate and dissolve them in 50ml of deionized water to form solution A, take 5.1mmol of sodium ferrocyanide decahydrate and 15mmol of sodium tartrate and dissolve them in 50ml of deionized water to form solution B. Use a peristaltic pump to drip solution A into solution B at a flow rate of 5ml / min, while ensuring that the stirring speed is 800r / min. After the addition is completed, stir for 16h and then age for 24h to obtain a Zn-based Prussian blue cathode material with a chemical formula of Na2Zn[Fe(CN)6].
[0101] The preparation method and testing method of the positive electrode sheet, negative electrode sheet and full battery of this embodiment are the same as those of Embodiment 1 and will not be repeated here.
[0102] Example 7
[0103] The difference between this embodiment and embodiment 1 is that the content of disodium tartrate is changed to 5 mmol, and the other steps remain unchanged.
[0104] Example 8
[0105] The difference between this embodiment and embodiment 1 is that the content of disodium tartrate is changed to 10 mmol, and the other steps remain unchanged.
[0106] Example 9
[0107] The difference between this embodiment and embodiment 1 is that the content of disodium tartrate is changed to 20 mmol, and the other steps remain unchanged.
[0108] Comparative Example 1
[0109] The difference between this comparative example and Example 1 is that no disodium tartrate is added to solution A and solution B, and the other steps remain unchanged.
[0110] Comparative Example 2
[0111] The difference between this comparative example and Example 1 is that 5 mmol of MnSO4 and 15 mmol of disodium tartrate are dissolved in 100 ml of deionized water to form solution A, and 5.1 mmol of sodium ferrocyanide decahydrate and 15 mmol of disodium tartrate are dissolved in 100 ml of deionized water to form solution B. The remaining steps remain unchanged. The SEM image of the Mn-based Prussian blue positive electrode material of Comparative Example 2 is shown in FIG. Figure 6 As shown, Figure 6 The right part of the middle is a partial enlarged view of the left part. Figure 2 and Figure 6 It can be seen that in Comparative Example 2, due to the low concentration of disodium tartrate, good complexation cannot be achieved and a good salt-in-water structure cannot be formed, which will lead to an increase in the content of crystal water in the material and a significant change in the particle size from 500-800nm in Example 1 to 5-10μm in Comparative Example 2.
[0112] Comparative Example 3
[0113] The difference between this comparative example and Example 1 is that 5 mmol of MnSO4 and 15 mmol of disodium tartrate are dissolved in 30 ml of deionized water to form solution A, and 5.1 mmol of sodium ferrocyanide decahydrate and 15 mmol of disodium tartrate are dissolved in 30 ml of deionized water to form solution B. The remaining steps remain unchanged. Too high a concentration of disodium tartrate may result in the precipitation of disodium tartrate after the reaction of the material, which will be adsorbed and remain on the surface of the material, reducing the main material part of the reagent providing capacity, which is not conducive to mass production.
[0114] The electrochemical performance results of the button-type full cells of Examples 1 to 9 and Comparative Examples 1 to 3 are shown in Table 1, and the mass percentage of the thermogravimetric water content is shown in Table 2.
[0115] Thermogravimetric water content analysis method: Under an inert atmosphere, heat the material to 500°C at a rate of 10°C / min, measure the mass loss of the material during the process, and obtain the weight loss rate, which can effectively characterize the adsorbed water and crystallized water content of Prussian blue materials.
[0116] Table 1 Electrochemical performance of the batteries of various embodiments and comparative examples
[0117]
[0118] Table 2 Thermogravimetric water content of each embodiment and comparative example by weight
[0119]
[0120]
[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0122] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing a Prussian blue positive electrode material, characterized in that: include: dissolving a transition metal salt and a first disodium tartrate in a first deionized water to obtain a first solution; dissolving sodium ferrocyanide decahydrate and second disodium tartrate in second deionized water to obtain a second solution; adding the first solution to the second solution to obtain a suspension; The suspension is stirred and aged to obtain the Prussian blue positive electrode material.
2. The method for preparing a Prussian blue positive electrode material according to claim 1, characterized in that: The usage ratio of the transition metal salt, the first disodium tartrate, and the first deionized water is 1 mol: (1-4) mol: (40-90) ml.
3. The method for preparing a Prussian blue positive electrode material according to claim 1 or 2, characterized in that: At least one of the following conditions is met: A. The transition metal salt includes at least one of a Mn salt, a Fe salt, a Co salt, a Ni salt, a Cu salt, and a Zn salt; B. The transition metal salt includes at least one of sulfate, chloride, acetate, acetylacetonate and oxalate.
4. The method for preparing a Prussian blue positive electrode material according to claim 1, characterized in that: The usage ratio of the sodium ferrocyanide decahydrate, the second disodium tartrate, and the second deionized water is 1 mol: (1-4) mol: (40-90) ml.
5. The method for preparing a Prussian blue positive electrode material according to claim 1, characterized in that: At least one of the following conditions is met: A. the speed at which the first solution is added to the second solution is 1 ml / min-10 ml / min; B. The first solution is added to the second solution while stirring at a speed of 500 r / min-1000 r / min.
6. The method for preparing a Prussian blue positive electrode material according to claim 1, characterized in that: At least one of the following conditions is met: A. The stirring time is 10h-20h; B. The aging time is 20-30h.
7. A Prussian blue positive electrode material, characterized in that: The positive electrode material is prepared by the method for preparing the Prussian blue positive electrode material according to any one of claims 1 to 6.
8. A positive electrode sheet, characterized in that: The invention comprises the Prussian blue positive electrode material as described in claim 7.
9. A sodium ion battery, characterized in that: Including the positive electrode sheet as described in claim 8.
10. An electrical device, characterized in that: Including the sodium ion battery as described in claim 9.